Репрезентація феномену сакральності засобами кінематографу (на прикладі творчості Андрія Тарковського) - Сокол, Я. В.; Sokol, Y. V.; Колосок, Т. С.; Kolosok, T. S. (Східноєвропейський національний університет імені Лесі Українки, 2013)
статті досліджено репрезентацію сакральності засобами кіномистецтва у фільмі російського режисера Андрія Тарковського «Андрій Рубльов», адже уявлення про сакральне формуються під впливом багатьох факторів, у тому числі кіномистецтва. Акцентовано увагу на кінематографічних засобах передачі сакральності: звуки, чорно-біла плівка, вода, вогонь, молоко, ікона «Трійці», дзвін. Цей фільм, по суті, – символічний код, покликаний «схопити» невидиме у видимому, тобто зобразити феномен сакральності за посередництвом ситуацій і речей світу повсякденного. In the article the authors investigate representation of the sacralness phenomenon by cinematographic art in the film of Russian stage-director Andrei Tarkovskii «Andrei Rubl’ov». Actuality of the raised problem grows in the situation of culture desacralisation, when proclamation of religious dogmas becomes, to a great extent, the function of art. Phenomena world, due to which the noumenal world is comprehended, is being hidden in the real world. The task of a real artist, to В. Ivanov’s mind, is exposure in already existing reality the other one, more real, as things of the real lower order are participating in the reality of the higher order, and are its symbols. The stage-director Andrei Tarkovskii tried to reveal invisible in visible, and in his films represents sacralness using cinematographic means. In the article attention is accented to cinematographic means of sacralness presentation: sounds, black-and-white film, water, fire, milk, Trinity icon, bell. Water is a clearing symbol, white color is a color of blessing, cleanness and peace, due to which audience feels warmness and God's grace. Considerable place in the film is taken to the image of way, road, motion. The way to understanding of sacral, way to selfcomprehension. Tarkovskii uses sounds for representing of sacralness atmosphere. Sounds are carefully thought out symbolic image of reality, they are the sounds of nature (sounds of thunderstorm, rain, wind), and sounding of things, poetic and musical creations. Andrei Tarkovskii’s film «Andrei Rubl’ov» is, in fact, the symbolic code which is called to «comprehend» invisible in visible, i. e. to represent the phenomenon of sacralness by the means of situations and things of the everyday world, in fact an object comprehended as sacral becomes the symbol of something other-worldly, and, as a result, opens slightly this mysterious world for a man. The stage-director gives an opportunity to the audience to interpret everything seen by them on the screen independently; in fact the eternal symbols used in the film are given in collective unconscious.
Representation of the Sacralness Phenomenon by Cinema Means (Using the Example of Andrei Tarkovskii’s Work)
Keywords: сакральність; sacralness; кінематограф; cinema; символ; symbol